ASEAN Comprehensive Investment Agreement SEBAGAI PEDOMAN DALAM KEBIJAKAN PENANAMAN MODAL DI INDONESIA - Farhan Abel Septian Rachmadani (Program Magister Ilmu Hukum Universitas Pancasila, 2022)
Investment has a significant role in the economic development of developing countries. The countries must create a conducive investment ecosystem to attract investors, such as economic opportunity, political stability, and legal certainty. As a member of the ASEAN, Indonesia ratified the ASEAN Comprehensive Investment Agreement through Presidential Regulation no. 49 of 2011 concerning the Ratification of the ASEAN Comprehensive Investment Agreement on August 8, 2011. The ASEAN Member States agreed to enforce ASEAN Comprehensive Investment Agreement as a manual of legal protection for ASEAN investors to invest in the ASEAN Member States. Therefore, it is necessary to look at the readiness of national law to carry out progressive investment liberalization